2009
DOI: 10.1016/j.neuron.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal Neurons in Macaque Ventral Premotor Cortex with Mirror Properties: A Potential Mechanism for Action Suppression?

Abstract: SummaryThe discovery of “mirror neurons” in area F5 of the ventral premotor cortex has prompted many theories as to their possible function. However, the identity of mirror neurons remains unknown. Here, we investigated whether identified pyramidal tract neurons (PTNs) in area F5 of two adult macaques exhibited “mirror-like” activity. About half of the 64 PTNs tested showed significant modulation of their activity while monkeys observed precision grip of an object carried out by an experimenter, with somewhat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
253
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(283 citation statements)
references
References 50 publications
(38 reference statements)
27
253
0
3
Order By: Relevance
“…Mirror neurons do not fire in response to a simple presentation of objects, including food. Most of them do not respond or respond only weakly to the observation of the experimenter performing a motor act (for example, grasping) without a target object 7 .…”
Section: The Parieto-frontal Mirror Networkmentioning
confidence: 99%
“…Mirror neurons do not fire in response to a simple presentation of objects, including food. Most of them do not respond or respond only weakly to the observation of the experimenter performing a motor act (for example, grasping) without a target object 7 .…”
Section: The Parieto-frontal Mirror Networkmentioning
confidence: 99%
“…The remaining MNs respond to the observation and execution of dissimilar actions (e.g., to the sight of food being placed on a surface, but the act of grasping food to eat) and have been termed logically-related MNs. The existence of suppression MNs -units that fire during action performance, but are inhibited during the observation of similar actions (e.g., Kraskov et al, 2009) -further complicates matters. Rather than 'mirror' observed actions, such units appear to systematically prevent mirroring.…”
Section: Do Mirror Neurons 'Mirror'?mentioning
confidence: 99%
“…Moreover, examination of the early data reveals that 'pantomimed' actions (performed without objects) evoked responses in many MNs, albeit more weakly than object-directed actions (Gallese et al, 1996). Indeed, a more recent study found that 79% of MNs modulated their firing rate in response to pantomimed actions (Kraskov et al, 2009). …”
Section: Do Mirror Neurons Encode Goals?mentioning
confidence: 99%
“…Here, for the sake of completeness, I will briefly mention other interesting response characteristics which have been observed. These include specificity for mouth actions [21], sensitivity to whether actions are performed close to or further away from the monkey [6], response suppression to observed actions [42], sensitivity to mimed grasps [42], viewdependence [5] and sensitivity to the grasped object's reward value [4].…”
Section: Response Characteristics Of Mirror Neurons and Their Relevanmentioning
confidence: 99%
“…Indeed, until recently, a clear difference between the macaque mirror neuron data and human data from TMS and neuroimaging experiments was that the former demonstrate mirror responses to goal-directed actions, while the latter show mirror responses to actions both with and without a goal. However, Ferrari et al [21] described mouth mirror neurons which responded to actions without a goal, while Kraskov et al [42] found mirror neurons which responded to mimed actions; thus the conclusion that mirror neurons only respond to goal-directed actions is no longer secure. The sensorimotor account of mirror neuron properties explains this aspect of the difference between monkey and human data by comparing their learning histories:…”
Section: Suggestions For Future Researchmentioning
confidence: 99%